The dead room - Graham, Heather (Don Mills, Ont. : MIRA Books : 2007., 2007)
A year ago, archaeologist Leslie MacIntyre barely survived the lower Manhattan explosion of Hastings House that killed Matt, her fiancé. In the ensuing months, she's had to come to terms with not only her loss, but with her unsettling new ability to communicate with ghosts. Now Leslie has returned to the site of the explosion to conquer her fears, and investigate a newly discovered burial ground. In this place, restless spirits hold the secrets of past injustice--and a very real conspiracy with deadly designs on the city's women. By night, Matt visits Leslie's dreams, sometimes offering clues. But by day, it's Matt's cousin Joe who she is helped by--and attracted to. As she is drawn closer to the heart of darkness that is Hastings House, she must face the power of an evil mind alone in a place where not even the men she loves can save her.
cat
Keywords: New York (N.Y.) -- Fiction; Detective and mystery stories, American; Suspense fiction, American; Paranormal fiction, American